Diagnostic Utility of IGF2BP1 and Its Targets as Potential Biomarkers in ETV6-RUNX1 Positive B-Cell Acute Lymphoblastic Leukemia - Sharma, Gunjan; Boby, Elza; Nidhi, Thakur; Jain, Ayushi; Singh, Jay; Singh, Archna; Chattopadhyay, Parthaprasad; Bakhshi, Sameer; Chopra, Anita; Palanichamy, Jayanth Kumar (Frontiers in Oncology, 2021)
Around 85% of childhood Acute Lymphoblastic Leukemia (ALL) are of B-cell origin and characterized by the presence of different translocations including BCR-ABL1, ETV6-RUNX1, E2A-PBX1 and MLL fusion proteins. The current clinical investigations used to identify ETV6-RUNX1 translocation include FISH and fusion transcript specific PCR. In the current study we assessed the utility of IGF2BP1, an oncofetal RNA binding protein, that is over expressed specifically in ETV6-RUNX1 translocation positive B-ALL to be used as a diagnostic marker in the clinic. Further, public transcriptomic and Crosslinked Immunoprecipitation (CLIP) datasets were analyzed to identify the putative targets of IGF2BP1. We also studied the utility of using the mRNA expression of two such targets, MYC and EGFL7 as potential diagnostic markers separately or in conjunction with IGF2BP1. We observed that the expression of IGF2BP1 alone measured by RT-qPCR is highly sensitive and specific to be used as a potential biomarker for the presence of ETV6-RUNX1 translocation in future.